Experimental and numerical study of flow around a wind turbine rotor. (1st January 2013) - Dobrev, Ivan; Massouh, Fawaz; Memon, Asif
An improved model of an actuator surface is proposed, representing the flow around a wind turbine. This model was developed in conjunction with a Navier-Stokes solver using a blade element method for the calculation of power and wake development. Blades have been replaced with thin surfaces, and a boundary condition of 'pressure discontinuity' has been applied with rotor inflow and blade-section characteristics. The proposed improvement consists of applying tangential body forces along the chord, in addition to normal body forces resulting from pressure discontinuity along the blade cross-section. The proposed model has been validated for the flow around a horizontal-axis wind turbine. The results obtained from the proposed model are compared with the experimental results obtained from PIV-wind tunnel techniques. The comparison has displayed the necessity of the proposed model for accurate reproduction of the wake behind rotor. The rapidity of calculation, in comparison to full-geometry modelling, appears to be promising for wind farm simulations.